Wiera Gran - Zmarz-Koczanowicz, Maria (Poland : Studio Filmowe Largo, 2012)
Did a well-known cabaret singer from the Warsaw ghetto tarnish her reputation with the collaboration with Gestapo? This question recedes into the background as the director follows Agata Tuszyńska, the author of Oskarżona: Wiera Gran. Reconstructing the artist’s wartime and post-war life, the film touches upon the issue of moral judgment that is often too easy to pass – both for those who have never experienced the hell of war and for those who survived and need unambiguous assessment.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films